Carbon Disclosure, Contextual Factors, and Information Asymmetry: The Case of Physical Risk Reporting. Issue 4 (8th August 2019) - Schiemann, Frank; Sakhel, Alice
Abstract: The paper focusses on the reporting of climate change-related physical risks. Drawing on data from the CDP questionnaire for 717 European companies over three years (2011–2013) we find that information asymmetry is generally smaller when firms report about their physical risks. Furthermore, we find that reporting of a higher exposure to physical risks is associated with lower information asymmetry for firms falling under the regulation of the EU Emissions Trading Scheme, whereas for other firms the direction of the relationship reverses. We can rule out that our results are driven by other climate change-related risk disclosures and by disclosures about opportunities arising from climate change. This study is not only relevant because it attests the materiality of climate change-related physical risks. Moreover, we show how a contextual factor – in this study: whether a company falls under climate change-related regulation – moderates the direction of the relationship between reported information and information asymmetry.